O processo educativo e a formação identitária - Penno, Rosemeri Galvão (2009)
The aim of this research is to explore the following theme: the implications of the educational process into the formation of identity. It focuses on the development of identity, observing its process of construction, its implications and relationship with the educational process. Robert Daunis' concept of identity was used as a reference and we approached the concepts of "self" and individualization. After we looked at the formation of personality according to Freudian psychoanalytic theory that determines the dialectic formation of identity, arguing that personality and identity are simultaneous structures. The psychosexual phases of development and of psyche into ego, super-ego and "id" formation were also considered. Paul Ricoeur is another mentioned author with the theme of personal identity. He analyses three fundamental phases: introspection, identifying process and establishment of identity. The next step was the analysis of the educational process to construct identity. The basis is the comprehension that the formation of human being is unconditionally connected to educational process and to the understanding of its ideological aspects. It was important to show the place of the curriculum on this process of learning, the influences of means of communication and also many different styles of education and its influences, as well as the educational aims. We observed that the construction of identity is directly related to the educational process, so that educational efforts that are responsible and proper, will try hard to get total well-being for children and pupils, in the physical, intellectual, psycho-social and spiritual aspects always together with the pupils' family which has a special role. Finally, a reflection about the implications, influences and consequences of the educational process to the formation of the identity with contributions from psychology of education by Reinhard and Anne Marie Tausch were made. They focus the characteristics of personality as an educational objective. In this way it was possible to conclude that the family's way of living together with the school work will create other possibilities of communication in which everyone will learn, reconsidering all values and trying to live new community experiences.